COPD: Die wichtigsten Komorbiditäten - Pizarro, Carmen; Skowasch, Dirk (DMW - Deutsche Medizinische Wochenschrift, 2019)
Patients with chronic obstructive pulmonary disease (COPD) are frequently afflicted by comorbidities. In terms of quality of life, health status and prognosis, comorbid conditions negatively impact the lives of the sufferers. The link between these diseases is complex and comprises manifold considerations: it may be mediated by common risk factors, notably smoking, or by sequelae of COPD, like physical inactivity. Moreover, systemic inflammatory processes and mechanistic considerations seem to play a central role. As symptomatology is frequently overlapping, comorbid diseases tend to be overlooked. In consequence, they require proactive diagnostic approaches. Treatment should adhere to current guidelines, irrespective of the presence of COPD.
Keywords: chronisch obstruktive Lungenerkrankung (COPD); Komorbidität; kardiovaskuläre Erkrankung; Depression; Osteoporose